An Overview on the Theme of Courage in “The Perfect Storm” - Keleş, Aybike (Antalya Akev Universitesi, 2024)
“The Perfect Storm”, directed by Wolfgang Petersen, is a film adaptation of a novel of the same name by Sebastian Junger. The movie narrates the exceptional skills and courage of the six crew members, led by Captain Tyne, as they challenge the treacherous waters and violent storms of the North Atlantic Ocean. Starting with the small obstacles experienced by the sailors at the beginning, the story turns into an adventure that challenged their strength and courage. Despite completing their tasks in the final successfully, the crew is defeated by the great power of nature and sinks into the depths of the ocean. Nevertheless, the courage and skills they demonstrated throughout their journey distinguish them from the rest of the people and make them the heroes of their community. In the context of the cinematic narration, this paper examines how the actors demonstrate courage in the face of challenges, thereby reflecting the theme of bravery. This paper benefited from the philosophical perspectives of Osho and Joseph Campbell. The various stages a hero goes through according to the work titled The Hero With a Thousand Faces by Campbell, discussed as the focal points of the study.